Appraisal Analysis of Attitude Type in Instagram Residential Advertisement - Maharani, Valentina Yudistia (Language Horizon: Journal of Language Studies, 2024)
Housing developers compete to promote their houses through different media platforms because of the positive prospects in the housing sector. Instagram is a social media site commonly utilized for marketing different types of houses. Housing advertising posts employ taglines to convey the advertiser’s perspective on their residential properties. The attitude domain of appraisal theory, as described by Martin & White (2005), is utilized to differentiate between various sorts of attitudes found in housing adverts. The taglines of housing commercials were analyzed using the qualitative descriptive method. The findings indicate that home advertising taglines employ attitudes of judgement, affect, and appreciation, as well as a mix of affect-judgement and affect-appreciation attitudes. Housing advertisement taglines utilize the judgment to express social esteem attributes such as normality and tenacity. The judgement attitude is the predominant perspective utilized in housing advertising taglines. Moreover, advertisers employ the power of emotion to evoke a sense of joy in potential buyers when promoting housing. Moreover, the house that is being promoted is evaluated based on its appreciation.